PENERAPAN STRATEGI DIRECTED LISTENING THINKING ACTIVITY (DLTA) UNTUK MENINGKATKAN KETERAMPILAN MENYIMAK TEKS NARASI SISWA PADA PELAJARAN BAHASA INDONESIA KELAS III DI SDN 006 PASIR SIALANG - Nur Widiatuljannah; Putri Hana Pebriana; Fadhilaturrahmi; Iis Aprinawati; Yenni Fitra Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed at describing the increase of student listening skill through Directed Listening Thinking Activity strategy at the third grade of State Elementary School 006 Pasir Sialang, Bangkinang District, Kampar Regency. It was a classroom action research. The subjects of this research were a teacher and 25 of the third-grade students at State Elementary School 006 Pasir Sialang. This research was conducted for two cycles and every cycle comprised two meetings. Observation and written test were the techniques of collecting the data. Based on the research findings, the implementation of Directed Listening Thinking Activity strategy could increase student listening skill. Before the action, student listening skill was 57,22% with low category. After the action was conducted in the first cycle, student listening skill was 81% with good enough category. It increased in the second cycle to 92% with good category. Therefore, it could be concluded that the implementation of Directed Listening Thinking Activity strategy could increase student listening skill on Caring for Animals and Plants theme at the third grade of State Elementary School 006 Pasir Sialang, Bangkinang District, Kampar Regency.